Environmentally Friendly Nanoporous Polymeric Gels for Sustainable Wastewater Treatment - Tarek M. Madkour; Rasha E. Elsayed; Rasha A. Azzam (Gels)
Environmentally friendly nanoporous gels are tailor-designed and employed in the adsorption of toxic organic pollutants in wastewater. To ensure the maximum adsorption of the contaminant molecules by the gels, molecular modeling techniques were used to evaluate the binding affinity between the toxic organic contaminants such as methylene blue (MB) and Congo red (CR) and various biopolymers. To generate nanopores in the matrix of the polymeric gels, salt crystals were used as porogen. The pores were then used to accommodate catalytic nickel (Ni0) nanoparticles. Under UV irradiation, the nanoparticles demonstrated the effective adsorption and photocatalytic degradation of both the methylene blue and Congo red dyes, achieving removal efficiencies of up to 90% for MB and 80% for CR. The thermodynamic analysis suggested a spontaneous endothermic dissociative adsorption mechanism, which implies the oxidative catalytic degradation of the dyes. The kinetic modeling suggested a pseudo-second-order model, while the model for intra-particle diffusion revealed that Congo red diffuses faster than methylene blue. MB adsorption followed a Langmuir isotherm, while CR adsorption followed a linear isotherm. The results confirm that dye molecules initially undergo physisorption and subsequent dissociative adsorption. The products of the catalytic degradation of methylene blue continue to be absorbed on the surface of the nanoparticles, while those of Congo red switch to preferential desorption.